Neurological damage in SARS-CoV-2 infections - Vega-Fernández, Jorge Arturo (2021)
The current Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic has severely impacted the economy and health care system in more than 180 countries around the world in an unprecedented event, which since its inception has resulted in countless case reports focusing on the potentially fatal systemic and respiratory manifestations of the disease. However, the full extent of possible neurological manifestations caused by this new virus is not yet known. Understanding the interaction of SARS-CoV-2 with the nervous system is essential to assessing likely short- and long-term pathologic consequences. This review seeks to gather and discuss evidence on the occurrence of neurological manifestations and/or nervous system involvement in SARS- CoV-2 infected patients.